Sidescan sonar survey (300 kHz) during R/V Heincke cruise HE478 in the German Bight with link to raw data files - Svenja Papenmeier; H Christian Hass (PANGAEA, 2019)
Sidescan sonar data were collected during R/V Heincke cruise HE478 with a towed multi pulse Edgetech 4200-MP. Data recording was executed along 92 parallel profiles in North Sea within German EEZ. The survey speed was 4-5 knots and the swath set to 280 / 460 m to obtain a resolution of 0.25 cm / ~1 m along track. In total 700 km^2 were area-wide mapped. The interpreted sediment distribution map of this data area published in the GeoSeaPortal of the Federal Maritime and Hydrographic Agency (Papenmeier, S., Hass, H.C., Propp, C., Thiesen, M., Zeiler, M.: Verteilung der Sedimenttypen auf dem Meeresboden in der deutschen AWZ (1:10.000). www.geoseaportal.de, 2018).